Apolipoprotein M can discriminate HNF1A‐MODY from Type 1 diabetes. Issue 2 (21st January 2013) - Mughal, S. A.; Park, R.; Nowak, N.; Gloyn, A. L.; Karpe, F.; Matile, H.; Malecki, M. T.; McCarthy, M. I.; Stoffel, M.; Owen, K. R.
Abstract Aims Missed diagnosis of maturity‐onset diabetes of the young (MODY) has led to an interest in biomarkers that enable efficient prioritization of patients for definitive molecular testing. Apolipoprotein M (apoM) was suggested as a biomarker for hepatocyte nuclear factor 1 alpha (HNF1A)‐MODY because of its reduced expression in Hnf1a–/– mice. However, subsequent human studies examining apoM as a biomarker have yielded conflicting results. We aimed to evaluate apoM as a biomarker for HNF1A‐MODY using a highly specific and sensitive ELISA. Methods ApoM concentration was measured in subjects with HNF1A‐MODY (n = 69), Type 1 diabetes (n = 50), Type 2 diabetes (n = 120) and healthy control subjects (n = 100). The discriminative accuracy of apoM and of the apoM/HDL ratio for diabetes aetiology was evaluated. Results Mean (standard deviation) serum apoM concentration (μmol/l) was significantly lower for subjects with HNF1A‐MODY [0.86 (0.29)], than for those with Type 1 diabetes [1.37 (0.26), P = 3.1 × 10–18) and control subjects [1.34 (0.22), P = 7.2 × 10–19). There was no significant difference in apoM concentration between subjects with HNF1A‐MODY and Type 2 diabetes [0.89 (0.28), P = 0.13]. The C‐statistic measure of discriminative accuracy for apoM was 0.91 for HNF1A‐MODY vs. Type 1 diabetes, indicating high discriminative accuracy. The apoM/HDL ratio was significantly lower in HNF1A‐MODY than other study groups. However, this ratio did not perform well in discriminating HNF1A‐MODY from either Type 1 diabetes (C‐statistic = 0.79) or Type 2 diabetes (C‐statistic = 0.68). Conclusions We confirm an earlier report that serum apoM levels are lower in HNF1A‐MODY than in controls. Serum apoM provides good discrimination between HNF1A‐MODY and Type 1 diabetes and warrants further investigation for clinical utility in diabetes diagnostics.